Premature and preterm premature rupture of membranes in adolescent compared to adult pregnancy - Sergije Marković; Gordana Bogdanović; Anis Cerovac (Medicinski glasnik, 2019)
Aim: To compare the prevalence of premature rupture of membranes (PROM) and preterm premature rupture of membranes (PPROM) between adolescent and adult pregnancies, and the influence of gestational age and adolescent pregnancy on the frequency of occurrence of PROM and PPROM. Methods: This prospective study included 300 pregnant patients, 13 to 35 years of age, divided into two groups. The first group consisted of 150 pregnant women aged 13-19 (experimental group) and the second group consisted of 150 pregnant women aged 20-35 (control group). Results: There was a statistically significant higher incidence of both PPROM and PROM in the group of adolescent pregnant women compared to adult pregnant women (p<0.000001). Preterm delivery with PPROM was significantly more common in the group of adolescent pregnant women (p<0.004). Term delivery with PROM was statistically significantly more common in the adolescent pregnancy group than in the adult pregnancy group (p<0.001). Term delivery with PROM was statistically significantly more common than preterm delivery with PPROM in the group of adolescent pregnant women (p<0.0001). Conclusion: Adolescent pregnancy has a greater impact on the frequency of PROM and PPROM.
Keywords: fetal membranes; gestation; teenagers